Phonological Awareness and Reading: An Alternative Interpretation of the Literature from a Clinical Perspective - Malicky, Grace V.; Norman, Charles A. (Alberta Journal of Educational Research, 1999)
Many researchers have concluded that there is a strong causal relationship between phonological awareness and reading, and that deficiency in phonological awareness is a major factor in reading problems. This article provides an alternative interpretation based on a critical analysis of the research literature and three clinical case studies. On the basis of our results, we hypothesize that rather than phonemic awareness per se, what seems to be essential to learning to read is that children develop an understanding of the connections between oral and written language. At the macrolevel this involves an understanding that written words represent words in oral language. At the microlevel it involves understanding that letters in written words stand for phonemes in spoken words.